The Relationship of Family Role With Smoking Behaviour in Adolescent - Ambo Anto; Firman Telaumbanua; Sapriadi S; Nurul Fuadah (PT.Mantaya Idea Batara, 2024)
This study aimed to determine the relationship between family roles and smoking behavior in young men at Tut Wuri Handayani Senior High School Makassar. The research design used a cross-sectional approach where the role of the family is the independent variable, and smoking behavior is the dependent variable. This research has been carried out at SMA Tut Wuri Handayani Makassar. The population is all male students in class I and class II. A sample of 50 respondents was obtained by total sampling technique. Based on the results of the study, it was found that as many as 18 (81.8%) respondents assessed the role of the family as good and had good smoking behavior; on the contrary, 4 (18.2%) respondents rated the role of the family as good but had less smoking behavior. The results of statistical tests using the Chi- Square test obtained the value of X2 hit = .000 < 0.05. So the conclusion is Ho is rejected, or Ha is accepted, meaning that there is no relationship between family roles and smoking behavior in young men at Tut Wuri Handayani High School Makassar. It can be concluded that there is a relationship between family roles and smoking behavior in young men at Tut Wuri Handayani High School Makassar.